A Comparison of the Effects of Alpha and Medical-Grade Honey Ointments on Cutaneous Wound Healing in Rats. (3rd November 2016) - Paydar, Shahram; Akrami, Majid; Dehghanian, Amirreza; Alavi Moghadam, Roshanak; Heidarpour, Mohsen; Bahari Khoob, Amir; Dalfardi, Behnam
Abstract : Introduction . This study compared the healing efficacy and possible adverse effects of topical Alpha and medical-grade honey ointments on cutaneous wounds in rats. Methods . To conduct the study, 22 male Sprague-Dawley rats were randomly allocated into two equal groups: (1) rats with Alpha ointment applied to the wound surface area and (2) rats with medical-grade honey ointment applied to their wounds. The ointments were applied daily during the 21-day study period. Wound contraction was examined photographically with images taken on days 0, 7, and 21 after wounding. The healing process was histopathologically assessed using skin biopsies taken from the wound sites on days 7 and 21. Results . No statistically significant difference in mean wound surface area was observed between the two study groups. According to histopathological assessment, a significant reduction in the amount of collagen deposition (P value: 0.007) and neovascularisation (P value: 0.002) was seen in the Alpha-treated rats on day 21. No tissue necrosis occurred following the application of Alpha ointment. Conclusion . Daily topical usage of Alpha ointment on a skin wound can negatively affect the healing process by inhibiting neovascularization. Topical Alpha ointment can reduce the possibility of excessive scar formation by reducing collagen deposition.